All-printed triboelectric nanogenerator. (February 2018) - Seol, Myeong-Lok; Han, Jin-Woo; Moon, Dong-Il; Yoon, Kyung Jean; Hwang, Cheol Seong; Meyyappan, M.
Abstract: Mechanical energy harvesters have not much benefited from the significant advantages of additive manufacturing techniques because the functional materials are not compatible with most printable schemes. In this work, a triboelectric nanogenerator is designed and demonstrated only by additive manufacturing methods. The all-printed triboelectric nanogenerator (AP-TENG) combines the advantages of 2D and 3D printing technologies. The structural frame is formed by 3D printing as a core-shell structure, which effectively converts external vibrations into continuous sliding motion. The contact layers are created by 2D inkjet printing with precisely patterned grating structure. The nanoscale printed contact layers made on nanocellulose paper assure high output power and abrasion durability. The un-optimized AP-TENG here produces a maximum instantaneous voltage of 98.2 V and a maximum instantaneous current of 13.7 μA, with a threshold vibration amplitude of 1 mm and an optimum frequency range of 30–60 Hz. The AP-TENG can be autonomously manufactured by printers at the point-of-demand anywhere, making it particularly attractive in remote locations including other planets and the International Space Station where the logistics is complex and expensive. Graphical abstract: Highlights: Mechanical energy harvesters have not much benefited from the significant advantages of additive manufacturing techniques because of material and process compatibility issues. All-Printed triboelectric nanogenerator is developed combining advantages of 2D and 3D printings. High output power and abrasion durability are experimentally verified.